The alleviating effects of salicylic acid application against aluminium toxicity in barley (Hordeum vulgare) roots - VARDAR, FİLİZ (SPRINGER, 2016)
Aluminium (Al) toxicity is one of the major growth limiting factors that affects large agricultural areas resulting in reduced crop production in acid soils. The present study aims to investigate alleviating effects of salicylic acid (SA) on Al toxicity in barley (Hordeum vulgare L.) roots. The roots were exposed to 20 mu M AlCl3 with or without SA (5 and 10 mu M) for 72 h. In an alternative group, roots were pre-treated with 5 mu M and 10 mu M SA for 24 h, and then they were exposed to 20 mu M AlCl3. To evaluate the ameliorating effects of SA on Al toxicity some cellular stress responses were investigated including root elongation, Al uptake, loss of plasma membrane integrity, mitotic abnormalities, superoxide dismutase activity, peroxidase activity, total protein content and DNA fragmentation. The obtained results suggested that both pre-treatment and co-treatment of 10 mu M SA could alleviate Al-induced toxicity in barley roots in relation to inhibition of Al uptake and activation of the antioxidant enzyme system.
Keywords: aluminium; Al uptake; antioxidant enzymes; barley; DNA fragmentation; salicylic acid; PROGRAMMED CELL-DEATH; CADMIUM TOXICITY; OXIDATIVE DAMAGE; DEFENSE SYSTEM; TOLERANCE; STRESS; ARABIDOPSIS; RESPONSES; HEAT; PHYTOTOXICITY